The effect of Internet+ -based extracurricular running exercise on students’ physical fitness - Bingyuan Liang; Liujin Wu (Scientific Reports)
Abstract The application of the Internet combined with extracurricular running exercise plays an important role in promoting the reform of school physical education teaching and the healthy development of students’ physical fitness. 2379 students of Guilin Medical College used the Flash Campus APP for 30 weeks of running exercise during the school period, and the Wilcoxon test and t-test were used to statistically test the data of 50 m, standing long jump, lung capacity, seated forward bending, height, and body weight; men’s pull-ups, 1,000 m; and women’s sit-ups, 800 m pre- and post-tests. The Z/t values of men’s 50 m, standing long jump, pull-ups, and lung capacity; women’s 50 m running, standing long jump, sit-ups, lung capacity, and sitting prone flexion after extracurricular running exercise were − 3.513, − 5.571, − 5.069, and − 3.397; − 2.419, − 6.015, − 6.493, − 8.077, and − 2.474, respectively, with a P < 0.05, significant difference. Men’s BMI, seated forward bending, 1000 m; women’s BMI, 800 m running Z/t values were − 1.693, − 0.829, − 1.68; − 0.579, − 1.417, respectively, P > 0.05, there is no significant difference. The combination of the Internet and extracurricular running exercise can effectively monitor students’ running data and improve their performance in the events of lung capacity, 50-meter run, standing long jump, men’s pull-ups, women’s seated body bends and sit-ups.